Optimizing feeding regimen of replacement gilts to improve their reproductive performance and retention rate of their first 2 parities - Jiajian Tan; Miaomiao Wang; Haiqing Sun; Chao Wang; Hongkui Wei; Siwen Jiang; Yuanfei Zhou; Jian Peng (Animal Nutrition, 2023)
The effects of age, body weight (BW), and backfat thickness (BF) of replacement gilts at first estrus and first mating on their subsequent reproductive performance and retention of their first 2 parities as sows was evaluated. A total of 3,025 Danish replacement gilts were categorized by farm (allocated to 4 farms), cross combination, age, BW and BF at first estrus and first mating, estrous cycle number at first mating, and flush feeding before first mating. The result shows that all the factors mentioned above were significantly associated with reproductive performance and retention rates of the first 2 parities. Farm 3 had more piglets born alive per litter (BA) (P < 0.05). Farms 3 and 4 had more healthy piglets per litter (HP) (P < 0.05). Farm 4 had the most piglets weaned per litter (PW) (P < 0.05). Landrace × Landrace × Yorkshire (L × L × Y) replacement gilts had the most total piglets born per litter (TB), BA, HP, PW and a higher retention rate of the 2 parities than Landrace × Yorkshire (L × Y) replacement gilts (P < 0.05). In addition, flush feeding before first mating had the most TB, BA, HP, PW, and a higher retention rate of the 2 parities than no flush feeding (P < 0.05). Because the effects of replacement gilts rearing parameters on reproductive performance traits differed, we used 100 replacement gilts as a unit and the total number of weaned piglets from the first 2 parities as a new index. Replacement gilts undergoing their first estrus between 180 and 210 d of age at 115 to 124.9 kg BW and 14 to 15 mm BF had significantly higher reproductive indexes for their first 2 parities per 100 replacement gilts. Replacement gilts that mated between 210 and 230 d of age at 140 to 149.9 kg BW and 15 to 16 mm BF had optimal reproductive indexes. These results provide a new insight into the complex relationships among these reproductive performance traits and may help guide successful management of replacement gilts as a pivotal starting point for future fertility and longevity of rearing herds.